Indigenous micropolitics of reconciliation in Jimaín, Colombia (2020)
The Colombian postconflict period requires titanic efforts on the part of the local government of the Arhuaco of the Sierra Nevada de Santa Marta, caught between their own ancestral battles and the demands of central government institutions that may not even reach this region to administer justice and reintegration for territorial peace building. The reintegration of Arhuaco ex-combatants into their home communities has posed one of the greatest challenges. The interaction between Arhuaco justice and the Special Jurisdiction for Peace adopted in March 2017 is crucial for their effective reincorporation. Examination of the experiences of a group of Arhuaco authorities that has succeeded in building peace in a territory plagued by paramilitary and guerrilla violence, the military action of the Colombian government, and the entry of mega-projects into the region reveals the obstacles and the individual and collective development opportunities that have shaped those experiences. El período posconflicto colombiano requiere esfuerzos titánicos por parte del gobierno local del Arhuaco de la Sierra Nevada de Santa Marta, atrapado entre sus propias batallas ancestrales y las demandas de las instituciones del gobierno central que quizás ni siquiera lleguen a esta región para administrar justicia y reintegración para la construcción de la paz territorial. La reintegración de los excombatientes de Arhuaco en sus comunidades de origen ha planteado uno de los mayores desafíos. La interacción entre la justicia de Arhuaco y la Jurisdicción Especial para la Paz adoptada en marzo de 2017 es crucial para su reincorporación efectiva. El examen de las experiencias de un grupo de autoridades de Arhuaco que ha logrado construir la paz en un territorio plagado de violencia paramilitar y guerrillera, la acción militar del gobierno colombiano y la entrada de megaproyectos en la región revela los obstáculos y las oportunidades individuales y colectivos de desarrollo que han dado forma a esas experiencias.